Enhancing broiler product consumption: the influence of consumer perceptions and information delivery—evidence from five Chinese provinces - Lin, Huiqi; Zhu, Chengfei; Yang, Haopeng; He, Jun (Frontiers in Sustainable Food Systems, 2024)
This study employs an economics scenario-based experimental approach to examine the influence of messaging on consumer perceptions of broiler products, with the goal of promoting consumption and sustainable development in the broiler industry. Given the quality, nutritional value, and environmental advantages of broiler products, as well as their importance in bolstering food security in China, the research engaged 416 consumers from five provinces. Twelve messaging strategies were devised based on information source and type to assess their impact on consumer perceptions. The findings of the experiment reveal that the credibility of the information source and the nature of the content significantly affect consumer perceptions of broiler products. Notably, consumer perceptions are more influenced when the information source is highly trusted, and the content is presented positively. Analytical information has a stronger impact on consumer perceptions than conclusive information. However, negative information can impede the enhancement of consumer perceptions. The study recommends enhancing information dissemination strategies, selecting platforms with high consumer trust, and promptly sharing positive analytical information regarding broiler products to improve consumer perceptions and increase consumption potential. This research establishes an empirical basis for the broiler industry, aiding industry practitioners and policymakers in gaining a better understanding of consumer behavior and formulating more efficient marketing and consumer education strategies. Enhancing consumer perceptions of broiler products and stimulating consumption potential supports the industry's sustainable growth and market potential exploitation. Furthermore, it provides insights and solutions for optimizing China's meat consumption structure and ensuring national food security.